Additions to the checklist of the ants (Hymenoptera: Formicidae) of Peru - Guénard, Benoit; Economo, Evan P. (Zootaxa, 2015)
A recent species checklist of the ants of Peru recorded 592 nominal species and 79 genera on the basis of a literature review. Here we complement the previously published checklist with the addition of 83 nominal species and six genera, including three genera recorded only from morphospecies. This increases the list of ants reported from Peru to at least 679 species and subspecies and 85 genera. We also modify the list of species known as endemic from Peru, discuss the historical importance of the Peruvian ant fauna in myrmecology, and highlight potential research for future studies.